Novel water-soluble starch hydrogel as well as preparation method and application thereof
The water-soluble starch hydrogel prepared by physical mixing and chemical treatment solves the problems of poor wound healing and safety of chemical reagents in existing hydrogel dressings, achieving efficient wound healing and green and safe preparation process.
Patent Information
- Application Number
- CN202510084696.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-20
AI Technical Summary
Existing hydrogel dressings are not effective in promoting wound healing, and chemical reagents introduced during preparation may produce safety issues with degradation products.
Water-soluble starch hydrogels were prepared by simple physical mixing, and the water-soluble starch was treated with cationization and aldehyde synthesis to form a hydrogel bound by Schiff base crosslinking.
The water-soluble starch hydrogel prepared has excellent mechanical properties, antibacterial properties and antioxidant properties, which can effectively promote wound healing, and the preparation process is green, safe and non-toxic.
Smart Images

Figure CN119875153A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a novel water-soluble starch hydrogel and a preparation method and application thereof, belonging to the technical field of functional composite materials. Background Art
[0002] Bacterial infection of diabetic wounds, long-term high levels of oxidative stress and hyperglycemia leading to serious complications are the biggest challenges in wound healing research. Wound dressings are considered an important component and there are many different types, including gauze, film, foam or hydrogel, which are designed to directly contact the wound, protect the wound from further damage or infection, and promote healing. Among these dressings, hydrogels are gaining more and more attention as an ideal candidate for treating and protecting wounds with long-term inflammation.
[0003] The hydrogel system proposed in current research mainly achieves a multifunctional strategy to promote wound repair by loading a variety of exogenous additives such as antimicrobial agents, bioactive substances and growth factors, but faces problems such as drug resistance, high cost and complex preparation and production process. On the other hand, hydrogels derived from petrochemical polymers that are chemically cross-linked, although they have good mechanical properties, are usually accompanied by poor biodegradability, unsatisfactory biocompatibility, and some side effects of cytotoxicity and chronic rejection.
[0004] The document "A multifunctional hydrogel based on nature polysaccharide fabricated by Schiff base reaction;DOI:10.1016 / j.eurpolymj.2023.112330" discloses the use of carboxymethyl chitosan (CMCS) and oxidized hyaluronic acid (OHA) to prepare multifunctional hydrogels; the document "Status and future scope of plant-based green hydrogels in biomedical engineering;DOI:10.1016 / j.apmt.2019.04.010" discloses the use of plant-based materials to prepare hydrogels using Schiff base reaction; Patent CN118384315A discloses the use of dextran and sodium hyaluronate to prepare composite hydrogels, which can be used for wound repair. The above technical solutions all require the use of two or more raw materials when preparing hydrogels. Although the prepared hydrogels have good strength, they are actually not conducive to wound healing and recovery, and the chemical reagents (such as cross-linking agents) introduced in the preparation process may produce safety issues of degradation products during use. The preparation method of the water-soluble starch hydrogel provided by the invention only requires simple physical mixing, and no exogenous additives are used in the preparation process, so the method is green, safe and has no toxic side effects.
[0005] A renewable water-soluble starch with a compact, spherical and dendritic structure was discovered from sweet cereals. It contains a large number of hydroxyl groups on its surface and has unique functional properties such as excellent water retention, low intrinsic viscosity and good stability. Water-soluble starch can provide energy to skin cells by stimulating ATP production and cell metabolism, leading to increased production of hyaluronic acid and collagen. Water-soluble starch, which has the same structure as the skin, is the most effective energy source for skin cells and has multiple functions such as moisturizing, repairing, empowering, and anti-aging. In recent years, the unique hyperbranched dendritic nanostructure has made water-soluble starch an excellent carrier for lipophilic bioactive compounds. However, research on the preparation and application of water-soluble starch hydrogels has not yet appeared.
[0006] Therefore, developing a natural, renewable, multifunctional hydrogel that uses only water-soluble starch as the hydrogel material and does not add exogenous additives is of great significance for wound dressings. Summary of the invention
[0007] In order to solve the above problems, the present invention uses water-soluble starch to prepare cationized water-soluble starch and aldehyde-treated water-soluble starch, and on this basis, prepares water-soluble starch hydrogel. The hydrogel prepared by the present invention has simple and natural components, and has good mechanical properties on the basis of being able to efficiently promote wound healing.
[0008] The first object of the present invention is to provide a method for preparing a water-soluble starch hydrogel, comprising the steps of:
[0009] (1) mixing water-soluble starch and water, adding ethylenediamine, reacting; then adding 2,3-epoxypropyltrimethylammonium chloride, reacting; after the reaction, adding ethanol, precipitating, and drying to prepare a cationic water-soluble starch;
[0010] The water-soluble starch and water are mixed, sodium periodate is added, and the mixture is reacted; after the reaction is completed, ethylene glycol is added, dialyzed, and dried to prepare the aldehyde-modified water-soluble starch;
[0011] (2) preparing an aqueous solution obtained by preparing a cationized water-soluble starch and a aldehyde-containing water-soluble starch, and adding the cationized water-soluble starch aqueous solution to the aldehyde-containing water-soluble starch aqueous solution to react and obtain a water-soluble starch hydrogel.
[0012] In one embodiment, the water-soluble starch hydrogel is formed by combining cationized water-soluble starch and aldehyde-treated water-soluble starch through Schiff base cross-linking.
[0013] In one embodiment, the ratio of water-soluble starch, water and ethylene glycol in step (1) is 1-10 g: 200-300 mL: 2-20 mL;
[0014] The molar ratio of 2,3-epoxypropyltrimethylammonium chloride to water-soluble starch is 1:1-20;
[0015] Optionally, the molar ratio of 2,3-epoxypropyltrimethylammonium chloride to water-soluble starch is 1:10-20;
[0016] Preferably, the molar ratio is 1:14-16.
[0017] In one embodiment, the ratio of water-soluble starch to water in step (1) is 1-10 g: 50-500 mL;
[0018] The molar ratio of water-soluble starch to sodium periodate is 1 to 4:1.
[0019] In one embodiment, in the water-soluble starch hydrogel of step (2), the mass ratio of the cationic water-soluble starch to the aldehyde-containing water-soluble starch is 1-10:1-5.
[0020] Optionally, the mass ratio of the cationic water-soluble starch to the aldehyde-soluble starch is 1 to 2:1; preferably, the mass ratio is 2:1.
[0021] In one embodiment, the preparation method of water-soluble starch comprises:
[0022] The su1 sweet grains are crushed and mixed with water, centrifuged, and the first supernatant is collected; the pH value of the first supernatant system is adjusted, centrifuged, and the second supernatant is collected; the second supernatant system is adjusted, centrifuged, and the third supernatant is collected, boiled, allowed to stand, and then centrifuged to collect the fourth supernatant; excess anhydrous ethanol is added to the fourth supernatant, the supernatant is allowed to stand, filtered, and dried to obtain water-soluble starch.
[0023] In one embodiment, the preparation method of water-soluble starch comprises:
[0024] The su1 sweet grains are crushed and mixed with water, centrifuged, and the first supernatant is collected; the pH value of the first supernatant system is adjusted, centrifuged, and the second supernatant is collected; the second supernatant system is adjusted, centrifuged, and the third supernatant is collected, boiled, allowed to stand, and then centrifuged to collect the fourth supernatant; excess anhydrous ethanol is added to the fourth supernatant, the supernatant is allowed to stand, filtered, and dried to obtain water-soluble starch.
[0025] In one embodiment, the preparation method of water-soluble starch comprises:
[0026] Take corn, add 5 times the mass volume of deionized water to it, soak it at 4°C overnight; beat it, and pass it through a 300-mesh sieve; add deionized water to the filter residue and beat it again, pass it through a 300-mesh sieve, collect the filtrate twice, and remove the precipitate after the filtrate is allowed to stand at 4°C;
[0027] The pH of the liquid was adjusted to 4.9 with acetic acid, and the liquid was allowed to stand at 4°C for 2 hours. The liquid was centrifuged and the supernatant was collected. The pH of the clear liquid was adjusted to 7.0 with Na2CO3 solution, and the clear liquid was boiled in a boiling water bath for 30 minutes. The clear liquid was allowed to stand at 4°C for 2 hours, and the supernatant was collected after centrifugation.
[0028] Under stirring, add anhydrous ethanol to the supernatant until the volume fraction of ethanol in the solution is 75%, and let it stand at 4°C for 2 hours; filter the mixed solution, rinse the filter cake with anhydrous ethanol, dissolve the filter cake in water again, perform a secondary alcohol precipitation process, and then spread the filter cake naturally to dry to obtain water-soluble starch.
[0029] The second object of the present invention is to provide a water-soluble starch hydrogel prepared by any of the above methods.
[0030] In one embodiment, the liquid absorption swelling rate of the water-soluble starch hydrogel is 100% to 300%, the adhesion force reaches 400 to 2500 mN, and the hardness reaches 100 to 300 g.
[0031] The third object of the present invention is to provide application of any of the above methods or the above hydrogels in the biomedical field.
[0032] In one embodiment, the application includes preparing wound repair materials, drug delivery materials, tissue filling materials, and hemostatic materials.
[0033] The fourth object of the present invention is to provide a wound repair product, wherein the product contains the water-soluble starch hydrogel.
[0034] In one embodiment, the product is a dressing for promoting healing of diabetic chronic wounds.
[0035] The fifth object of the present invention is to provide a method for improving the wound repair effect of hydrogel, using water-soluble starch to prepare hydrogel, comprising the steps of:
[0036] (1) mixing water-soluble starch and water, adding ethylenediamine, reacting; then adding 2,3-epoxypropyltrimethylammonium chloride, reacting; after the reaction, adding ethanol, precipitating, and drying to prepare a cationic water-soluble starch;
[0037] The water-soluble starch and water are mixed, sodium periodate is added, and the mixture is reacted; after the reaction is completed, ethylene glycol is added, dialyzed, and dried to prepare the aldehyde-modified water-soluble starch;
[0038] (2) preparing an aqueous solution obtained by preparing a cationized water-soluble starch and a aldehyde-containing water-soluble starch, and adding the cationized water-soluble starch aqueous solution to the aldehyde-containing water-soluble starch aqueous solution to react and obtain a water-soluble starch hydrogel.
[0039] Beneficial effects of the present invention
[0040] The water-soluble starch hydrogel provided by the present invention is formed by combining cationic water-soluble starch and aldehyde-soluble starch through Schiff base cross-linking; the water-soluble starch hydrogel prepared by the present invention has a liquid absorption swelling rate of 100-300%, a 11h degradation rate of 26.54±1.36-39.90±1.96%, an adhesion force of 400-2500mN, a hardness of 100-300g, and has excellent antibacterial properties and an excellent wound healing effect;
[0041] Specifically:
[0042] (1) The water-soluble starch hydrogel of the present invention uses water-soluble starch as a raw material, so it is more natural, green and safe, so that the hydrogel does not contain exogenous additives, such as metal compounds, growth factors, antibiotics or nanoparticles, and has intrinsic antibacterial, antioxidant and immunomodulatory properties, which synergistically promote the healing of chronic wounds. Water-soluble starch is a highly branched soluble α-D-glucan connected by α-1,4 and α-1,6 glycosidic bonds. Due to the short average chain length and high branching degree, it has structural characteristics such as a dendritic branching pattern with tight outside and loose inside and a small particle size. The molecular structure has a large number of hydroxyl groups, which can undergo acylation, oxidation and carboxymethylation reactions, and can also form hydrogen bonds with water molecules, so it has excellent water retention. Water-soluble starch is the storage form of glucose in the human body and is also the main energy substance required for skin metabolism. Water-soluble starch, which has the same structure as the skin, is the most effective energy source for skin cells and has multiple functions such as moisturizing, repairing, empowering, anti-aging, immunomodulation and macrophage stimulation activity. The grafted quaternary ammonium salt groups have good antibacterial activity, and the added acetaldehyde groups enhance the antioxidant activity and adhesion of the hydrogel. The present invention provides a simple and effective method for preparing a multifunctional natural hydrogel dressing, and has great potential for promoting the healing of chronic diabetic wounds.
[0043] (2) The preparation method of the water-soluble starch hydrogel provided by the present invention is green, safe and non-toxic by simple physical mixing, without any exogenous additives in the preparation process. It solves the problems of drug resistance, high cost and complex preparation and production process faced by most of the current studies on hydrogels with synergistic effects of multiple exogenous additives such as antibacterial agents, bioactive substances and growth factors.
[0044] (3) The water-soluble starch hydrogel provided by the present invention is formed by combining cationic water-soluble starch and aldehyde-soluble starch through Schiff base cross-linking, has antibacterial and antioxidant properties, good adhesion and rheological properties, and has biocompatibility for removing active oxygen and immunomodulation. The water-soluble starch hydrogel avoids the limitations of petrochemical polymer hydrogels, such as poor biodegradability, unsatisfactory biocompatibility, and some cytotoxicity and chronic rejection side effects. The results show that the water-soluble starch hydrogel of the present invention accelerates the healing process of diabetic wounds, and the wound healing rate is 1.76 times that of commercially available dressings. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a scanning electron microscope image of the water-soluble starch hydrogel prepared in Example 1 at 100 μm.
[0046] Figure 2 This is a scanning electron microscope image of the water-soluble starch hydrogel prepared in Example 2 at 100 μm.
[0047] Figure 3 The infrared absorption spectra of the water-soluble starch hydrogels prepared in Example 1 and Example 2 are compared.
[0048] Figure 4 The liquid absorption swelling rate curves of the water-soluble starch hydrogels prepared in Example 1 and Example 2 are shown.
[0049] Figure 5 The degradation rate curves of the water-soluble starch hydrogels prepared in Example 1 and Example 2 are shown.
[0050] Figure 6 The adhesion force / displacement curves of the water-soluble starch hydrogels prepared in Example 1 and Example 2 are shown.
[0051] Figure 7 The hardness of the water-soluble starch hydrogel prepared in Example 1 and Example 2 was measured.
[0052] Figure 8 The following are the curves showing the change of storage modulus and loss modulus over time during the continuous jump change of strain of the water-soluble starch hydrogel prepared in Example 1 and Example 2.
[0053] Fig. 9 The pictures are of the inhibition zones of the water-soluble starch hydrogels prepared in Examples 1 and 2 against Staphylococcus aureus and Escherichia coli.
[0054] Fig.10 Representative photos of the water-soluble starch hydrogel prepared in Example 2 applied to the wound of a diabetic mouse model on days 0, 3, 7, and 14.
[0055] Fig.11 This is the adhesion curve of the water-soluble starch hydrogel prepared in Comparative Example 1.
[0056] Fig.12 This is the wound healing effect of the water-soluble starch hydrogel prepared in Comparative Example 1. DETAILED DESCRIPTION
[0057] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0058] The raw materials used in the examples are:
[0059] su1 sweet grains were purchased from Beijing Agricultural Science Institute;
[0060] 2,3-Epoxypropyltrimethylammonium chloride was purchased from Sigma-Aldrich.
[0061] Test method:
[0062] 1. Swelling rate and degradation rate detection method:
[0063] The swelling rate and degradation rate of the hydrogel are determined by soaking the sample in a PBS solution and weighing it at predetermined time intervals. After the freshly prepared hydrogel is freeze-dried, the sample is accurately weighed (recorded as W0) and then soaked in PBS at 37°C, pH 7.4. At predetermined time intervals, the hydrogel is removed from the PBS solution. After gently absorbing excess surface moisture with a moistened filter paper, the weight is recorded as Wp. Repeat this process until the hydrogel reaches water absorption equilibrium. The swelling rate calculation formula is as follows:
[0064] Wherein, Wp and W0 represent the weight of the initial freeze-dried hydrogel and the swollen hydrogel, respectively.
[0065] Accurately weigh the freshly prepared hydrogel sample (denoted as W f ), and then immersed in PBS at 37°C, pH 7.4. At predetermined time intervals, the hydrogel was removed from the PBS solution. The excess surface water was gently absorbed with a moistened filter paper and the weight was recorded as W. r The degradation rate calculation formula is as follows:
[0066] Among them, W f and W r represent the weight of initial hydrogel and remaining hydrogel, respectively.
[0067] 2. Adhesion force / displacement curve detection method:
[0068] The hydrogel was placed between two identical glass plates, with an application area of 1 cm 2 The thickness of the applied film was 1 mm and the film was pressed for 5 minutes to obtain sufficient adhesion. The relationship between the adhesion and displacement of the hydrogel was recorded using a universal material tensile testing machine to characterize its adhesion performance. All tests were performed at a 2 mm min -1 The stretching is carried out at a constant speed.
[0069] The relationship between the adhesion force and displacement of the hydrogel was recorded using a tensile tester to characterize the adhesion properties of the hydrogel.
[0070] 3. Hardness testing method:
[0071] The hardness of the hydrogel was analyzed using a TA.XTC-20 texture analyzer with a 36 mm cylindrical probe and a test speed of 0.05 mm / s.
[0072] 4. Storage modulus and loss modulus detection method:
[0073] The rheological properties of the hydrogels were investigated using an Anton Paar rheometer (MCR model 302) by dynamic amplitude sweep, frequency sweep, viscosity measurement, and strain sweep experiments. Static shear rheology measurements were used to determine the apparent viscosity (η) of the hydrogel samples at 25 °C as a function of shear rate (γ) increasing from 0.01 s-1 to 100 s-1. Cyclic strain sweep (thixotropy) experiments were performed to observe the strain changes of the hydrogels between 1% and 1000% to evaluate their self-healing ability. Based on the strain sweep results, the linear viscoelastic range was set to 0.1% and a small amplitude oscillatory shear mode was used. The temperature was maintained at 25 °C to measure the changes in the storage modulus (G') and loss modulus (G") in the frequency range of 0.1 Hz to 100 Hz.
[0074] 5. Antibacterial effect detection method:
[0075] Place two sterile Oxford cups (Φ7.8×6×10mm) evenly in each sterile Petri dish with a diameter of 70mm. Then pour about 15mL of melted LB solid medium into the Petri dish, wait for the medium to solidify, and take out the Oxford cup. Add 50μL of Escherichia coli (10 7 CFU / mL) and 50 μL of Staphylococcus aureus (10 6 CFU / mL) bacterial solution, spread evenly. Then add 150μL of sterile hydrogel extract solution with a concentration of 4mg / mL to each well. Add buffer to the microwells as a control experiment. After covering the culture dish lid, seal the sealing film, place it in a 4℃ refrigerator for pre-diffusion for 2h, and then place it in a 37℃ incubator for 24h. Take pictures to record the inhibition zone.
[0076] 6. Wound healing effect detection method:
[0077] Type 1 diabetes was induced in male Kunming mice by subcutaneous injection of 1% streptozotocin (STZ) solution at 60 mg / kg. One week after STZ injection, blood glucose levels were measured using a Sinovac blood glucose meter. Mice with blood glucose levels exceeding 11.1 mmol / L were selected to establish a wound infection model. For the full-thickness infected wound model, a 1 cm diameter wound was created on the back of each mouse using surgical scissors. The diabetic mice with wound infection were randomly divided into three treatment groups (n=6): control group; commercial wound dressing (Tegaderm) group; hydrogel CPG2-Gel group (wound diameter 1 cm, sample loading 0.2 g). Photos of the wounds were taken on days 0, 3, 7, 10, and 12. ImageJ software was used to measure and analyze the wound area.
[0078] Example 1: Preparation of water-soluble starch hydrogel
[0079] 1. The preparation method of water-soluble starch comprises the following steps:
[0080] Take a certain mass of corn, add 5 times the mass volume of deionized water to it, soak it at 4°C overnight; beat it, and pass it through a 300-mesh sieve; add deionized water to the filter residue and beat it again, pass it through a 300-mesh sieve, collect the filtrate twice, and remove the precipitate after the filtrate is allowed to stand at 4°C;
[0081] The pH of the liquid was adjusted to 4.9 with acetic acid, and the liquid was allowed to stand at 4°C for 2 hours. The liquid was centrifuged and the supernatant was collected. The pH of the clear liquid was adjusted to 7.0 with Na2CO3 solution, and the clear liquid was boiled in a boiling water bath for 30 minutes. The clear liquid was allowed to stand at 4°C for 2 hours, and the supernatant was collected after centrifugation.
[0082] Under stirring, add anhydrous ethanol to the supernatant until the volume fraction of ethanol in the solution is 75%, and let it stand at 4°C for 2 hours; filter the mixed solution, rinse the filter cake with anhydrous ethanol, dissolve the filter cake in water again, perform a secondary alcohol precipitation process, and then spread the filter cake naturally to dry to obtain water-soluble starch.
[0083] 2. The preparation method of water-soluble starch hydrogel comprises the following steps:
[0084] (1) Cationized and aldehyde-treated water-soluble starch
[0085] 5 g of water-soluble starch was mixed with 250 mL of deionized water, and then 15 mL of ethylenediamine was added. The mixture was stirred at 50° C. for 4 h, and then 2,3-epoxypropyltrimethylammonium chloride was added. The molar ratio of water-soluble starch to 2,3-epoxypropyltrimethylammonium chloride was 1:1. The mixture was stirred at 50° C. for 2 h at a speed of 200 rpm. After the reaction was completed, the mixture was diluted with 3 times ethanol and stored at 4° C. to obtain a precipitate. The precipitate was dried in an oven to obtain a cationic water-soluble starch.
[0086] The water-soluble starch was dissolved in deionized water (0.05 g / mL), sodium periodate was added, the molar ratio of the water-soluble starch to the sodium periodate was 2:1, the mixture was stirred at 30°C (speed 200 rpm) for 2 h, 10% (v / v) ethylene glycol was added, the mixture was dialyzed for 2 days, and the mixture was freeze-dried to obtain the hydroformylated water-soluble starch;
[0087] (2) Preparation of hydrogel
[0088] A 0.1 g / mL cationized water-soluble starch solution was prepared by using a cationic water-soluble starch, and a 0.05 g / mL aldehyded water-soluble starch solution was prepared by using a aldehyded water-soluble starch;
[0089] 0.1 g / mL of cationic water-soluble starch solution was added dropwise to 0.05 g / mL of aldehyded water-soluble starch solution at a volume ratio of 1:1, and a cross-linking reaction was carried out at 30° C. for 10 minutes to obtain a water-soluble starch hydrogel.
[0090] Example 2: Preparation of water-soluble starch hydrogel
[0091] On the basis of Example 1, in step (1) of Example 2, the molar ratio of water-soluble starch to 2,3-epoxypropyltrimethylammonium chloride is changed to 1:15, and the remaining steps are consistent with Example 1 to prepare a water-soluble starch hydrogel.
[0092] Example 3: Performance testing of water-soluble starch hydrogel
[0093] 1. Water-soluble starch property detection
[0094] The water-soluble starch, cationized water-soluble starch, aldehyde-modified water-soluble starch prepared in Example 1 and the cationized water-soluble starch prepared in Example 2 were taken to detect the weight-average molecular weight (MW), average particle size, z-average root mean square radius (RZ), molecular density (ρ), polydispersity (PDI), degree of substitution and ζ potential (ζ). The results are shown in Table 1.
[0095] Table 1 Water-soluble starch property test
[0096]
[0097] The results show that the degree of substitution of the cationic water-soluble starch of Examples 1 and 2 increased from 18.50±0.50% to 38.15±1.67%, and the particle size increased from 85.27±1.86nm to 219.73±13.74nm. As the degree of substitution increases, the number of quaternary ammonium salt groups introduced into the water-soluble starch molecules increases, which leads to an increase in charge density. Higher charge density will increase the electrostatic repulsion between molecules, making the molecular chain more stretched, thereby increasing the particle size.
[0098] At the same time, the ζ-potential of the cationized water-soluble starch of Examples 1 and 2 increases from 5.77±0.77 to 28.78±4.32mV, because the quaternary ammonium cation (three methyl groups and one epoxypropyl group are connected to the N atom, and it carries a positive charge) exists in the 2,3-epoxypropyltrimethylammonium chloride molecule, which can increase the ζ-potential of the water-soluble starch derivative. The charged characteristic of quaternary ammonium salts gives water-soluble starch a certain antibacterial ability, because the positive charge carried by quaternary ammonium salts can attract each other with the negatively charged components on the surface of bacterial cell membranes, and the accumulation of quaternary ammonium salts on the cell membranes will interfere with the normal structure and function of the cell membranes.
[0099] On this basis, the molecular weights of the cationic water-soluble starch and the water-soluble starch after aldehyde derivatization in Examples 1 and 2 were reduced, because the water-soluble starch formed new functional groups by cleavage of glycosidic bonds during the derivatization reaction with 2,3-epoxypropyltrimethylammonium chloride and sodium periodate, respectively. Glycosidic bonds are chemical bonds connecting glucose units, and their cleavage will shorten the chain length of the water-soluble starch molecules, thereby reducing the molecular weight.
[0100] 2. Water-soluble starch property detection
[0101] (1) Scanning electron microscope
[0102] The water-soluble starch hydrogels prepared in Examples 1 and 2 were characterized using a scanning electron microscope. Figure 1 , Figure 2 The results show that the SEM image of the hydrogel is a typical porous microstructure, but the structure of the water-soluble starch hydrogel in Example 2 is relatively dense.
[0103] (2) Infrared absorption spectrum
[0104] The water-soluble starch hydrogels prepared in Examples 1 and 2 were characterized using infrared absorption spectroscopy.
[0105] The results are as follows Figure 3 As shown, at 1645cm -1 There is a very obvious stretching vibration absorption peak of imine bond (C=N), which is the infrared characteristic absorption peak of Schiff base. The results show that cationic water-soluble starch and aldehyde-modified water-soluble starch form hydrogel through Schiff base cross-linking.
[0106] (3) Swelling properties
[0107] Swelling performance is an important property that an ideal wound dressing should have. An ideal wound dressing should be able to absorb liquid and exudate on the wound surface and maintain appropriate humidity in the wound area to facilitate wound recovery. An ideal wound dressing should have a liquid absorption swelling rate of 100% to 900%.
[0108] The water-soluble starch hydrogels prepared in Examples 1 and 2 were placed in a PBS buffer solution, and their swelling properties were characterized by measuring the mass of the hydrogels at different time points.
[0109] The results are as follows Figure 4 As shown, the results show that as time goes by, the mass of the water-soluble starch hydrogels prepared in Example 1 and Example 2 gradually increases; after the immersion time reaches 6 hours, the mass of the hydrogel expands to about 200% of the initial mass, after which the swelling of the hydrogel reaches equilibrium and the mass no longer increases. The high swelling performance of the hydrogel in Example 2 is related to its porous structure and cross-linking bonds.
[0110] (4) Degradation rate
[0111] The water-soluble starch hydrogels prepared in Examples 1 and 2 were taken to detect the degradation rate of the hydrogels.
[0112] The results are as follows Figure 5 As shown, with the passage of time, the degradation rates of the water-soluble starch hydrogels prepared in Example 1 and Example 2 were 39.90±1.96% and 26.54±1.36% respectively after 11 hours; the degradation rate of the hydrogel in Example 2 was lower, which was due to its stronger cross-linking effect and more stable hydrogel structure.
[0113] (5) Adhesion
[0114] The water-soluble starch hydrogel prepared in Examples 1 and 2 was taken to detect the adhesion force / displacement curve of the hydrogel. The hydrogel was placed between two glass plates for a lap shear test, and the relationship between the adhesion force and the displacement was obtained by testing with a universal testing machine.
[0115] The results are as follows Figure 6 As shown, the maximum adhesion forces of the water-soluble starch hydrogels prepared in Example 1 and Example 2 under the same displacement conditions reached 433.68 mN and 2342.86 mN, respectively; it can be seen that the adhesion performance of the hydrogel in Example 2 is better than that in Example 1.
[0116] (6) Hardness
[0117] Moderately hard hydrogel dressings can provide certain mechanical protection for wounds, preventing external physical stimulation and bacterial invasion. At the same time, they fit well with the wound surface, do not cause additional pressure or friction damage to the wound, and promote wound healing.
[0118] The water-soluble starch hydrogels prepared in Examples 1 and 2 were taken to test the hardness of the hydrogels.
[0119] The results are as follows Figure 7 As shown, the hardness of the water-soluble starch hydrogels prepared in Examples 1 and 2 also exhibits characteristics similar to the adhesion performance, and the hardness increases with the increase of the degree of substitution; among them, the hardness of the hydrogel in Example 2 is the largest, reaching 288.98±2.14g.
[0120] (7) Storage modulus and loss modulus
[0121] The water-soluble starch hydrogels prepared in Examples 1 and 2 were taken, and the self-healing properties and viscoelastic behaviors of the water-soluble starch hydrogels prepared in Examples 1 and 2 were characterized by rheological measurements.
[0122] The results are as follows Figure 8As shown, according to the strain amplitude sweep test, 1% and 100% strains were selected for 5 cycle tests. When a large strain was applied, the storage modulus dropped significantly and was lower than the dissipation modulus, indicating that the network was broken. When the strain was switched to 1%, the network could recover, indicating that the storage modulus and dissipation modulus values were immediately and completely restored to their original state. Even after four repeated cycles, the modulus curve did not change significantly, indicating that the water-soluble starch hydrogel of the present invention has excellent self-healing ability.
[0123] (8) Antibacterial effect
[0124] The water-soluble starch hydrogel prepared in Examples 1 and 2 was used to detect its antibacterial effect on Staphylococcus aureus and Escherichia coli using the inhibition zone method.
[0125] The results are as follows Fig. 9 As shown, there are very clear inhibition zones on the bacterial plates treated with the water-soluble starch hydrogels prepared in Example 1 and Example 2. As the degree of substitution increases, the diameter of the inhibition zone gradually increases.
[0126] The above results prove that the water-soluble starch hydrogel of the present invention has a significant inhibitory effect on Staphylococcus aureus and Escherichia coli, and exhibits excellent antibacterial properties.
[0127] (9) Wound healing effect
[0128] The water-soluble starch hydrogels prepared in Examples 1 and 2 were used to detect their wound healing effects on diabetic mice (0, 3, 7, and 14 days).
[0129] The results are as follows Fig.10 As shown, the circular diabetic wounds were treated with the hydrogel of Example 2 and the commercially available Tegaderm dressing, and the wound healing was monitored after 3, 7 and 14 days. According to the digital photos of the wound closure marks, it can be observed that the diabetic wounds in the hydrogel of Example 2 and the commercially available hydrogel group gradually healed in a circular shape, and the hydrogel of Example 2 showed a better wound healing effect. During the 14-day observation period, the hydrogel of Example 2 significantly accelerated the healing of the wound.
[0130] Compared with the commercially available hydrogel group or the control group, the healing rate of the hydrogel in Example 2 was further improved statistically, reaching 70.77%, which was 1.76 times higher than the healing rate of the commercially available dressing. This shows that the water-soluble starch hydrogel prepared in Example 2 is an excellent hydrogel for promoting diabetic wound healing.
[0131] The hydrogel prepared in Example 2 has the following advantages compared with the pure starch-based hydrogel prepared from ordinary starch:
[0132] (1) The pure starch-based hydrogel prepared from ordinary starch has low strength and insufficient toughness, and usually needs to be modified by adding functional polymers to form a double network structure; while the water-soluble starch hydrogel prepared in Example 2 has higher strength and toughness, and when subjected to external force, it can disperse stress more evenly and has a stronger ability to resist deformation and rupture;
[0133] (2) The pure starch-based hydrogel prepared from ordinary starch has poor water absorption and water retention capabilities, which is not conducive to providing a more lasting moist environment for cell growth or wound healing. However, the branched structure and functional groups on the molecular surface of the water-soluble starch hydrogel prepared in Example 2 may enable it to have a higher water absorption capacity and can better retain moisture for a certain period of time. In a dry environment, the water retention performance may be better, which can provide a more lasting moist environment for cell growth or wound healing.
[0134] (3) The structure of the starch molecules may change when the pure starch-based hydrogel prepared from ordinary starch is exposed to high or low temperatures, which may affect the performance of the hydrogel and make it less stable. However, the water-soluble starch hydrogel prepared in Example 2 can maintain good network structure integrity and original function when faced with changes in temperature, pH value, etc.
[0135] (4) Factors such as the size and crystallinity of starch particles in the pure starch-based hydrogel prepared from ordinary starch will affect the recognition of the immune system and cause an inflammatory response; while the molecular structure of the water-soluble starch in the water-soluble starch hydrogel prepared in Example 2 has certain similarities with the carbohydrate substances in the body, and its immunogenicity, on the one hand, is conducive to maintaining the stability of the local immune environment, and on the other hand, has a certain anti-inflammatory effect, which can reduce the inflammatory response and promote tissue repair.
[0136] Comparative Example 1: Preparation of hydrogel using water-soluble starch and glutaraldehyde
[0137] Based on Example 2, 1 g of cationic water-soluble starch was dissolved in 10 mL of 25% glutaraldehyde aqueous solution, and mixed with a vortex mixer to obtain a water-soluble starch / glutaraldehyde hydrogel after thorough mixing.
[0138] Testing of properties of water-soluble starch glutaraldehyde hydrogel
[0139] (1) Adhesion
[0140] The water-soluble starch / glutaraldehyde hydrogel prepared in Comparative Example 1 was taken to detect the adhesion force / displacement curve of the hydrogel. The hydrogel was placed between two glass plates for a lap shear test, and the relationship between the adhesion force and the displacement was obtained by testing with a universal testing machine.
[0141] The results are as follows Fig.11As shown, the adhesion force of the water-soluble starch hydrogel prepared in Comparative Example 1 under the same displacement conditions reaches 3670 mN; it can be seen that the adhesion force of the hydrogel in Comparative Example 1 is greater than that in Examples 1 and 2.
[0142] (2) Wound healing effect
[0143] The water-soluble starch hydrogel prepared in Comparative Example 1 was used to test its healing effect on the wounds of diabetic mice (0, 3, 7, and 14 days). Fig.12 As shown, the water-soluble starch / glutaraldehyde hydrogel has too strong adhesion to the skin, penetrates into the skin and affects skin recovery, hindering dressing changes.
[0144] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a water-soluble starch hydrogel, characterized in that: Includes steps: (1) mixing water-soluble starch and water, adding ethylenediamine, reacting; then adding 2,3-epoxypropyltrimethylammonium chloride, reacting; after the reaction, adding ethanol, precipitating, and drying to prepare a cationic water-soluble starch; The water-soluble starch and water are mixed, sodium periodate is added, and the mixture is reacted; after the reaction is completed, ethylene glycol is added, dialyzed, and dried to prepare the aldehyde-modified water-soluble starch; (2) The aqueous solutions obtained by preparing cationized water-soluble starch and aldehyde-hydrated water-soluble starch separately are added into the aqueous solution of aldehyde-hydrated water-soluble starch to react and obtain a water-soluble starch hydrogel.
2. The method according to claim 1, characterized in that Step (1) In the preparation of cationic water-soluble starch, the ratio of water-soluble starch, water and ethylene glycol is 1-10 g: 200-300 mL: 2-20 mL; The molar ratio of 2,3-epoxypropyltrimethylammonium chloride to water-soluble starch is 1:1-20.
3. The method according to claim 1, characterized in that In step (1), in the preparation of the aldehyde-modified water-soluble starch, the ratio of the water-soluble starch to water is 1-10 g: 50-500 mL; The molar ratio of water-soluble starch to sodium periodate is 1 to 4:
1.
4. The method according to claim 1, characterized in that: In the water-soluble starch hydrogel of step (2), the mass ratio of the cationic water-soluble starch to the aldehyde-containing water-soluble starch is 1-10:1-5.
5. The method according to claim 1, characterized in that The preparation method of water-soluble starch comprises: The su1 sweet grains are crushed and mixed with water, centrifuged, and the first supernatant is collected; the pH value of the first supernatant system is adjusted, centrifuged, and the second supernatant is collected; the second supernatant system is adjusted, centrifuged, and the third supernatant is collected, boiled, allowed to stand, and then centrifuged to collect the fourth supernatant; excess anhydrous ethanol is added to the fourth supernatant, the supernatant is allowed to stand, filtered, and dried to obtain water-soluble starch.
6. The water-soluble starch hydrogel prepared by the method according to any one of claims 1 to 5.
7. Use of the method according to any one of claims 1 to 5 or the hydrogel according to claim 6 in the biomedical field.
8. The use according to claim 7, characterized in that: The applications include preparing wound repair materials, drug delivery materials, tissue filling materials, and hemostatic materials.
9. A wound repair product, characterized in that: The product contains the water-soluble starch hydrogel according to claim 6.
10. A method for improving the wound repair effect of hydrogel, characterized in that: The method for preparing a hydrogel using water-soluble starch comprises the following steps: (1) mixing water-soluble starch and water, adding ethylenediamine, reacting; then adding 2,3-epoxypropyltrimethylammonium chloride, reacting; after the reaction, adding ethanol, precipitating, and drying to prepare a cationic water-soluble starch; The water-soluble starch and water are mixed, sodium periodate is added, and the mixture is reacted; after the reaction is completed, ethylene glycol is added, dialyzed, and dried to prepare the aldehyde-modified water-soluble starch; (2) preparing an aqueous solution obtained by preparing a cationized water-soluble starch and a aldehyde-containing water-soluble starch, and adding the cationized water-soluble starch aqueous solution to the aldehyde-containing water-soluble starch aqueous solution to react and obtain a water-soluble starch hydrogel.
Citation Information
Patent Citations
Double-component hydrogel adhesive and preparation and application thereof
CN108753202A
Preparation method of transparent, anti-freezing and self-healing conductive hydrogel capable of being used for flexible electronics
CN116426004A
Hydrogel adsorbent based on interpenetrating network and preparation method and application thereof
CN117323977A
Antibacterial hydrogel based on Schiff base reaction as well as preparation method and application of antibacterial hydrogel
CN118662688A
Starch-based material having improved absorbent properties and process for the preparation thereof
EP0900806A1